2022
DOI: 10.1021/acsomega.1c06112
|View full text |Cite
|
Sign up to set email alerts
|

Visible-Light-Driven Carbon-Doped TiO2-Based Nanocatalysts for Enhanced Activity toward Microbes and Removal of Dye

Abstract: Solar-driven photocatalytic approach is an attractive, clean, and effective way for decontamination of water. In this work, visible-light-activated TiO 2 nanoflakes (TNFs) and carbondoped TiO 2 nanoflakes (C-TNFs) were synthesized via a facile hydrothermal route using different carbon sources. The assynthesized nanostructures were successfully characterized by powder X-ray diffraction (XRD), Fourier transform infrared (FT-IR) spectroscopy, scanning electron microscopy (SEM), and transmission electron microscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 77 publications
0
14
0
Order By: Relevance
“…In addition, it was found that adsorption capacity decreased with the increase in calcination temperature. Previous research demonstrated that the decoration of graphene on TiO 2 increases the pore size and surface area, which ultimately increase the adsorption capacity , …”
Section: Resultsmentioning
confidence: 99%
“…In addition, it was found that adsorption capacity decreased with the increase in calcination temperature. Previous research demonstrated that the decoration of graphene on TiO 2 increases the pore size and surface area, which ultimately increase the adsorption capacity , …”
Section: Resultsmentioning
confidence: 99%
“…Several researchers reported that the doped photocatalyst activity increases after non-metal doping, as the electronic structure has been modified to extend the absorption of the photocatalyst into the visible-light region [ 57 ]. Various studies have shown non-metal doping of TiO 2 , such as Nitrogen-doped TiO 2 [ 58 ], carbon-doped TiO 2 [ 59 , 60 , 61 ], sulfur-doped TiO 2 [ 62 , 63 ], boron-doped TiO 2 [ 64 ] and phosphorus-doped TiO 2 [ 65 ]. Vaiano et al studied recyclable visible-light active N-doped TiO 2 photocatalysts coated on glass spheres using a simple sol-gel method.…”
Section: Photocatalysis and Mass Transfermentioning
confidence: 99%
“… 4 However, due to its wide band gap ( E g = 3.2 eV), titania only responds to ultraviolet irradiation, which accounts for only ∼3–4% of the whole solar spectrum. 5 Hence, developing new visible light-active photocatalysts is of significant research and technological interest among the scientific community. 6 8 …”
Section: Introductionmentioning
confidence: 99%
“…The majority of research has so far focused on the titania (TiO 2 ) photocatalyst, which has a strong oxidizing ability and chemical stability . However, due to its wide band gap ( E g = 3.2 eV), titania only responds to ultraviolet irradiation, which accounts for only ∼3–4% of the whole solar spectrum . Hence, developing new visible light-active photocatalysts is of significant research and technological interest among the scientific community. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation